Identifying and targeting dormant cells in acute myeloid leukaemia - Yu, N. (2016)
Relapse in AML is thought to arise from dormant leukaemic cells that are characterised by low RNA synthesis activity, protected by the bone marrow (BM) niche, and may evade the effects of chemotherapeutic drugs. Our aim was to investigate agents which might be able to overcome chemoprotection by targeting the intrinsic apoptosis pathway. We developed in vitro assays to identify and characterise the dormant AML cells using combinations of markers, including the cell-division marker PKH26, leukaemia-associated phenotypes (LAPs), and dormancy markers. In a dormancy model based on 12-day AML/stroma co-culture, we have shown that the expression of some aberrant phenotypes can persist for several days. Also, after 12 days, some of the CD34+, PKH26high (dormant), and LAP+ (leukaemic) cells maintained their primitiveness and were still clonogenic. Furthermore, our chemosensitivity data showed that novel agents TG02, and BH3 mimetics ABT-737 and ABT-199, which inhibit the B-cell lymphoma 2 (BCL-2) family of anti-apoptotic molecules, could efficiently target BM niche-mediated chemoresistance, which is thought to be one of the main obstacles to traditional chemotherapy. We explored various candidate dormancy markers based on the low RNA, non-proliferative profile of dormant cells. Among those tested, the RNA synthesis marker Pyronin Y (PY), and an antibody to the transferrin receptor CD71 were the most reproducible in terms of marker expression and stability. We endeavoured to characterise cell dormancy on the molecular level by investigating gene expression in the PYlow (dormant) and PYhigh (proliferating) subsets and have obtained limited results. In summary, this study has identified and partly characterised dormant AML cells by development of in vitro assays, and has shown chemosensitivity to novel agents TG02, ABT-737 and ABT-199 in dormant leukaemia cells.